The Effect of Brand Image and Brand Trust on Repurchase Intention of Rexona Products in Surabaya - Nabila Mahlida; Ugy Soebiantoro (International Journal of Economics and Management Sciences, 2025)
This study is prompted by the reduction in the Rexona brand index in 2024, which coincided with several program-related mistakes that generated consumer dissatisfaction and led to a noticeable erosion of both brand image and brand trust. Such circumstances highlight the vulnerability of even well-established brands when faced with consumer discontent, as missteps in marketing campaigns or product related initiatives can have a lasting impact on how consumers perceive and evaluate a brand. For companies operating in highly competitive industries, these issues raise serious concerns, since negative brand perceptions and diminished trust are likely to undermine consumer loyalty, weaken brand equity, and reduce the likelihood of long-term purchasing behavior. Against this backdrop, the present research seeks to examine more deeply how brand image and brand trust contribute to shaping consumers repurchase intention for Rexona products in Surabaya, a city that represents a dynamic and diverse consumer market. To achieve this objective, the study adopted a quantitative research approach, applying the Partial Least Squares (PLS) method for statistical analysis. Data were obtained through purposive sampling, involving 110 respondents who were identified as active and cosistent user of Rexona products within the city of Surabaya. The findings of the research reveal that brand image shows a benefical effect on repurchase intention, while brand trust demonstrates a significant role in enhancing consumer willingness to engage in repeat purchases. These results emphasize that the synergy between a strong brand image and sustained consumer trust acts as a fundamental determinant for maintaining repurchase intention, particularly within highly competitive market environments.